Citizen science, accessibility, art & science, critical thinking, policy and engagement: thoughts and lessons learned from the REINFORCE experience - Angelidakis, Stylianos (2024)
REINFORCE (Research Infrastructures FOR Citizens in Europe) is a Research & Innovation Project, supported by theEuropean Union’s Horizon 2020 SwafS, ‘Science with and for Society’ work programme (GA872859). The project, which ran fromDecember, 2019, to November, 2022, engaged the public in a variety of innovative ways. Four citizen-science demonstrator projectswere developed on the world-leading Zooniverse platform, each focussing on a different area of frontier physics: gravitational waves;neutrino astronomy; particle physics; and muography. A range of art and science events were launched and undertaken. A data-sonification tool—sonoUno—was developed in order to improve the accessibility of the data used in the four demonstrator projects.A course on critical thinking and a history of the Second Scientific Revolution was provided on YouTube and in podcast form,while a senior-citizen-science course was designed, co-developed and implemented. These initiatives were supported by a detailedengagement plan, a dedicated communications and dissemination strategy, and a constantly evolving assessment and evaluationapproach. The experiences garnered during the project, in conjunction with consultations with project participants, volunteers andstakeholders, were built into the form of a policy roadmap explaining how to integrate citizen science into research infrastructuresin Europe. The roadmap identifies a series of policy objectives and related policy gaps, associated challenges and lays out a seriesof recommendations. This article describes the results of the REINFORCE project and draws together the experiences of each ofthe involved twelve partner organisations.